Предмет: Алгебра,
автор: Citi050
решите уравнение (х+2)(х-2)-(2х-3)^2=12х-3х^2
Ответы
Автор ответа:
0
x²-4-4x²+12x-9-12x+3x²=0
-13=0
нет решения
-13=0
нет решения
Автор ответа:
0
(х+2)(х-2)-(2х-3)^2=12х-3х^2,
(х² - 4) - (4х² - 12х + 9) = 12х - 3х²,
х² - 4 - 4х² + 12х - 9 - 12х + 3х² = 0,
-13 ≠ 0,
данное уравнение не имеет решения
(х² - 4) - (4х² - 12х + 9) = 12х - 3х²,
х² - 4 - 4х² + 12х - 9 - 12х + 3х² = 0,
-13 ≠ 0,
данное уравнение не имеет решения
Похожие вопросы
Предмет: Алгебра,
автор: neustrvictor3
Предмет: Алгебра,
автор: neustrvictor3
Предмет: Химия,
автор: MiWelson
Предмет: Математика,
автор: Аля09062005
Предмет: Математика,
автор: vityakolosovsky